A novel functionally graded bilayer membrane with excellent barrier function and in vivo osteogenesis promotion for guided bone regeneration - Li, Junxuan; Ding, Jiaxin; Zhou, Tao; Li, Bolun; Wang, Jingjing; Wang, Hanchi; Fu, Li (Frontiers in Pharmacology, 2024)
Guided bone regeneration (GBR) technology has been widely used as a reliable method to address alveolar bone defects. However, the existing resorbable guided bone regeneration membranes (GBRMs) are limited to maintain the osteogenic space effectively due to poor mechanical strength and rapid degradation rate, etc. By combining the phase inversion method and electrospinning method, functional grade bilayer membranes (FGBM) with gradient structure and composition of poly(lactic-coglycolic acid) (PLGA), nano-hydroxyapatite (nHA), and gelatin were fabricated in this study. This study comprehensively evaluated the physicochemical and biological properties of the prepared FGBM, encompassing structural and morphological characterization, mechanical properties, in vitro biodegradation, cell behaviors, and in vivo osteogenic bioactivity. The findings demonstrated the successful fabrication of PLGA/nHA/gelatin FGBM with an asymmetric structure, exhibiting enhanced hydrophilic, mechanical, and degradation properties. The inclusion of gelatin not only brought better biological integration, but also enhanced the binding affinity between electrospun fiber layer and phase inversion layer. The fabricated FGBM with a 30% nHA mass fraction and a PLGA/gelatin mass ratio of 1:1 exhibited both good barrier function and the optimal osteogenic bioactivities in vitro and in vivo. Consequently, our findings substantiated the viability of FGBM for guided bone regeneration.